OPTIMIZATION OF MODERN TREATMENT OF POST-TRAUMATIC DISEASES OF THE CORNEA - Kamilov Khalidjan Makhamadjanovich; Khudoyberganov Azizbek Ruzbaevich (Western European Studies, 2024)
Currently, one of the urgent tasks of preventive medicine and ophthalmology is to increase the effectiveness of rehabilitation measures in patients with diseases of the organ of vision, among which post-traumatic corneal damage occupies an important place. Cornea pathology accounts for 1/4-1/5 of all eye diseases. In 25-75% of cases, the disease process can end with consequences ranging from various blurs leading to vision loss or vision loss. It is especially relevant to research treatment methods aimed at accelerating the regeneration process and maintaining the transparency of the cornea in various diseases. In the search for the most effective methods of treating post-traumatic corneal damage, we focused on the positive features of using a low-frequency magnetic field
Keywords: cornea; eye damage; corneal ulcer